The Labor Market Consequences of Acquisitions - Jakob Beuschlein; Jósef Sigurdsson; Horng Chern Wong (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We study the effects of corporate acquisitions on workers using Swedish administrative data and document substantial, persistent earnings losses following acquisitions. These losses reflect both displacement and wage cuts among stayers from target firms. We find no evidence that increased monopsony power accounts for these wage cuts. Instead, they are concentrated in acquisitions where the acquiring-firm CEO sat on the board of the target prior to the transaction. Such acquisitions increase acquiring-firm profits and CEO pay, without affecting total employment or revenue, consistent with rent redistribution. Overall, acquisitions reduce wages and disrupt employment, with profit gains partly extracted from workers.
Keywords: G34; J23; J31; J42; J63; L25; 330; mergers and acquisitions; wages; layoffs; monopsony; firm performance; managers